If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -4m + 3 = 5 Reorder the terms: 6 + 3 + -4m = 5 Combine like terms: 6 + 3 = 9 9 + -4m = 5 Solving 9 + -4m = 5 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -4m = 5 + -9 Combine like terms: 9 + -9 = 0 0 + -4m = 5 + -9 -4m = 5 + -9 Combine like terms: 5 + -9 = -4 -4m = -4 Divide each side by '-4'. m = 1 Simplifying m = 1
| 5t+2=-33 | | 2x/5-2=6 | | 33c-14=-3-11c | | 33c-14=--11c | | 4x-12x=-36 | | 7(6+7)+x=8 | | -5(5x-5)=-225 | | 39=43 | | 12w+-6+w=32+4w+21 | | -3x+5(-3x-2)=-100 | | 3m-(-7)=10 | | 7w-8=27 | | (n+5)*10=1000 | | 16x+5=42 | | 2+3y-9=5y-7-2y | | 16x+5=-36 | | 11x+6=5x+18 | | (m-1)x^2+2mx+(m+2)=0 | | 3y-5x=8 | | 3(4x+5)-2=3x+4 | | 36=3/5 | | 12a+6-8a=88 | | -6v+3(v+3)=-21 | | -3x+7(-x-17)=-69 | | 12=-8+4m | | 7=3(u-3)-7u | | 9(a+-4)=64 | | 2.5=x/15 | | -33-3x=-8x+11 | | 2x-3=(-4) | | 8y+5=5+9y | | -18=2(y+3)-5y |